During the Soviet era and following the collapse of the USSR. How post-Soviet states are (re)building their tourism sector. The examples of Ukraine and Georgia - Nataliia Moroz (Via@)
No discourse on tourism geopolitics would be complete without one of the historic and landmark cases that affected the tourism industry on a global scale: that of tourism in the former Soviet Union. This gigantic country comprising 15 republics managed to build an unusual tourism tradition between mass domestic tourism and international tourism controlled by the single company Intourist.Following the dissolution of this geopolitical entity, the post-Soviet areas, representing today a particularly curious field of study, entered a new stage in the construction of their tourism sectors while at the same time providing new targets for international tourism. In terms of domestic and hospitality tourism, these are more specifically areas under permanent (re)construction as a result of not only historical and political changes, but also identity and remembrance discourses that, moreover, mark their respective heritage landscapes. Ukraine and Georgia are two such symbolic examples through their quest to ‘de-Sovietise’ their tourism dynamics by changes in political discourses leading, on the one hand, to a war of monuments and remembrance, but also, on the other hand, to a ‘mythologisation’ and a ‘folklorisation’ of their tourist areas.